2009
DOI: 10.1007/s10157-009-0172-8
|View full text |Cite
|
Sign up to set email alerts
|

Infective endocarditis in hemodialysis patients: clinical features, echocardiographic data and outcome

Abstract: In this largest reported confirmed IE series in dialysis patients in a developing country, mortality was very high; mitral valve was the most commonly affected valve. Staphylococcus species were the major causative organisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 15 publications
3
24
0
Order By: Relevance
“…Reported mortality of HD patients who underwent operation during the active phase of IE is high, [2][3][4] and perioperative management should be carefully planned based on previous experience. In our present study, clinical characteristics specific to our HD patients were pacemaker implantation is predicted after weaning from cardiopulmonary bypass (CPB), epicardial permanent pacing wires (atrial and ventricular) should be implanted intra-operatively, because a permanent intravascular device is a potential risk for recurrent IE in HD patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reported mortality of HD patients who underwent operation during the active phase of IE is high, [2][3][4] and perioperative management should be carefully planned based on previous experience. In our present study, clinical characteristics specific to our HD patients were pacemaker implantation is predicted after weaning from cardiopulmonary bypass (CPB), epicardial permanent pacing wires (atrial and ventricular) should be implanted intra-operatively, because a permanent intravascular device is a potential risk for recurrent IE in HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…1) Several previous studies have demonstrated high postoperative mortality (11%-80%) in HD patients who require surgical intervention for IE, [2][3][4] however, little information is available on the preoperative management of these patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implications of bacteremia in CVDs have been briefly outlined in Figure 1 and tabulated in Table 1. Large vegetation Congestive heart failure and stroke [59] Mitral and aortic valve vegetation Abscess formation [60] Bi-prosthetic valve infections Valve ring abscess and cuspal infections [62] Acute bacterial endocarditis Valve ring abscesses [63,64] and paravalvular leakage [66,67] Xenograft or mechanical valves Recurrent infections [79] Circulating endotoxemia Congestive heart failure [89,90] …”
Section: Clinical Implications Of Circulating Microbiome In Cvdsmentioning
confidence: 99%
“…ESRD patients receiving chronic hemodialysis were particularly prone to non-nosocomial IE [60][61][62] than those receiving peritoneal dialysis [63]. S. aureus and MRSA blood stream infections were more prevalent in hemodialysis patients [64].…”
Section: Infective Endocarditis (Ie)mentioning
confidence: 99%